Exploring dark tourism: the geographies of three selected UK sites - Figueiredo, Rita (2023)
This thesis serves to add to the current conceptualisation of dark tourism as a distinctive phenomenon within the wider tourism industry. Throughout history, and especially in today’s globalised and media-drive society, there has been an increasing interest to visit sites of past atrocities and tragedies (Dunkley et al., 2007). This study aims to critically examine the geographies of dark tourism across three selected UK sites, to effectively test the adaptability of the phenomenon of dark tourism across three deliberately different case studies. Also, the study aims to critically explore how to effectively conduct geographical research on the phenomenon of dark tourism. This thesis adopts a qualitative case study approach which utilises data collection methods of semi-structured interviews and observations. The thesis will be actively reflecting upon its methodology, to assess how to examine particular contextual aspects in which the phenomenon occurs. The chosen sites for this research project were the following: Jack the Ripper walking tours in London, Brodsworth Hall and Gardens in Doncaster, and Aberfan and its memorial garden and cemetery in South Wales. With these three examples, this thesis aims to address the complexities of implementing a set typology onto different sites with differing degrees of darkness.